Total toxic aldicarb residues in coffee fruits and beans after soil application of aldicarb at different intervals before harvesting - Rigitano, Renê L. O.; Souza, Júlio César de; Moraes, Maurício L. (Pesquisa Agropecuaria Brasileira, 2014)
This work examined the total toxic aldicarb residues in whole coffee fruits, roasted and non-roasted coffee rind and beans, after a soil application of Temik 15 G (20 ou 40 kg/ha) at different intervals before harvesting. The residues were extrated by blending the sample with a mixture of acetone and water, the aldicarb residues were oxidized to aldicarb sulfone by the addition of acetic acid to the extracting solvent. After appropriate cleanup of the extract on a florisil column, the pesticide residues were determined as aldicarb sulfone by gas chromatography utilizing a flame-photometric detector. The residues found in dried whole fruits were 0.06 ppm, 0.23 ppm, 0.38 ppm, 0.13 ppm and 0.05 ppm for dosage 16 kg/ha and 0.20 ppm, 0.53 ppm, 0.40 ppm, 0.20 ppm and 0.13 ppm (dosage 32 kg/ha), corresponding respectively to the application carried out at 15, 30, 45, 60 and 90 days before harvesting. The residue levels in the rind were much higher than in the beans; the residue concentration in the beans from all treatments was lower than the limit of detection by the analytical method used (0.02 ppm). The residue concentration in roasted rind from all treatments was lower than the limit of detection in roasted samples (0.03 ppm), which indicated that most of the residues were eliminated during the roasting process.